PENGARUH MODEL PEMBELAJARAN TTW (THINK TALK WRITE) TERHADAP KETERAMPILAN MENULIS KARANGAN PENDEK BERTEMA YOKU SOJI O SHIMASU SISWA KELAS XI IPA SMAN MODEL TERPADU BOJONEGORO - Ika Melisa Putri (Universitas Negeri Surabaya, 2020)
The ability to write essay is one of the important things in learning languages, included Japanese. However, based on interview tests conducted at the SMA Model Terpadu Bojonegoro, it was found that students ability to write are weak, so the Think Talk Write learning model was applied to improve students' writing abilities. Therefore, a TTW (Think Talk Write) learning model applied to make it easier for students to write essays. This research is a qantitative type of pure experimental research (true experiment design). In the control class drill and assignment method were used as learning model, while in the experimental class TTW (Think Talk Write) used as learning model. The data used are pre-test and post-test for the controlclass and student questionnaire responses for the experimental class. The results of this study are asym.sig. (2-tailed) 0.678> 0.05 then Ho is accepted and Ha is rejected, in other words there is no effect of the application of the Think Talk Write learning model to students' short essay writing skills. While it is known from the calculation results of the questionnaire studeents' responses to the TTW learning model that on average items 1 to 5 show sufficient criteria (41% -60%) very strong (81% -100%), and it can be concluded that the TTW learning model is suitable for applied in Japanese learning.